Agriculture through design approach and collaborative product development / Azmir Mamat Nawi and Muhamad Aiman Afiq Mohd Noor - Mamat Nawi, Azmir; Mohd Noor, Muhamad Aiman Afiq (Universiti Teknologi MARA, Kedah, 2018)
The attacks of Golden Apple Snails have ruined paddy plants and have caused losses to farmers. This is because they have to spend more time and money to transfer affected paddy plots by applying the infill process. This is a process where the affected paddy is transplanted on to another paddy plot. Thus, this problem has prompted the researchers to identify and understand this phenomenon. The researchers come out with the best prevention in controlling the G.A.S and have proposed a design to help the farmers to ease the problem faced by them currently. The researchers have also explored the problem and solution, evaluated the solution by investigating user behaviour and describe the solution through usability testing. Based on this research, the researchers have designed a hand tool to take the eggs of golden apple snails